2002
DOI: 10.1504/ijhrdm.2002.001032
|View full text |Cite
|
Sign up to set email alerts
|

Using Activity Theory in system development for entire organisations: the case of the Swedish Trade Union Confederation

Abstract: Activity Theory has, in recent years

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…In parallel, Kuutti (1996) identified that the narrow research focus of human-computer interaction (HCI) was problematic since the context was not included in the unit of analysis, and that activity theory was a potential solution to the problem. Activity theory has since found multiple application areas within both HCI and information system design (e.g., Pilemalm and Timpka 2002).…”
Section: Activity Theorymentioning
confidence: 99%
“…In parallel, Kuutti (1996) identified that the narrow research focus of human-computer interaction (HCI) was problematic since the context was not included in the unit of analysis, and that activity theory was a potential solution to the problem. Activity theory has since found multiple application areas within both HCI and information system design (e.g., Pilemalm and Timpka 2002).…”
Section: Activity Theorymentioning
confidence: 99%
“…Kuutti (1996) identified that the narrow research focus of human-computer interaction (HCI) was problematic since the context was not included in the unit of analysis, and that activity theory was a potential solution to the problem. Activity theory has since found multiple application areas within both HCI and information system design (e.g., Pilemalm and Timpka 2002), and in several domains of which one is EM (Chen et al 2013).…”
Section: Introduction To Activity Theorymentioning
confidence: 99%
“…Kuutti (1996) identi ed that the narrow research focus of human-computer interaction (HCI) was problematic since the context was not included in the unit of analysis, and that activity theory was a potential solution to the problem. Activity theory has since found multiple application areas within both HCI and information system design (e.g., Pilemalm and Timpka 2002), and in several domains of which one is EM (Chen et al 2013).…”
Section: Introduction To Activity Theorymentioning
confidence: 99%